Resenha de: The abolition of the Brazilian slave trade - Saéz, E. M. Garcia (Revista de História, 1971)
BETHELL (Leslie) . — The abolition of the Brazilictn slave trade, Brasil and the slave question 1807-1869. Cambridge at the University Press, 1970 (424 páginas).